2015
DOI: 10.4236/ojpm.2015.56027
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Health Beliefs, Knowledge and Life Habits among Women in Saudi Arabia

Abstract: Osteoporosis has been recognized as a major public health problem by healthcare providers in Saudi Arabia. The present study examines the osteoporosis knowledge, health beliefs, and some of the life habits in two different Saudi women's groups (with family history, and without family history), to find the association of their knowledge and health beliefs with their preventive practice. This is a descriptive cross-sectional study conducted among a convenience sample of 288 young age (20 to 40 years) women atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…Calcium intake is particularly important in postmenopausal and elderly women because calcium deficiency is associated with reduced bone density. Low calcium intake has been reported to be one of the risk factors for osteoporosis amongst Asian women [43], even though supplementation (i.e., calcium and vitamin D) may reduce the rate of bone loss and fracture in adults [44]. The low dairy and calcium intake of Chinese subjects in this study might be related to the prevalent perception that calcium causes renal stones, the high prevalence of lactose intolerance among Malaysian Chinese [45], the absence of dairy products as ingredients in Chinese dishes, aversion of the taste [46], and concerns about weight gain and the fat/cholesterol content of some calcium-rich foods [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium intake is particularly important in postmenopausal and elderly women because calcium deficiency is associated with reduced bone density. Low calcium intake has been reported to be one of the risk factors for osteoporosis amongst Asian women [43], even though supplementation (i.e., calcium and vitamin D) may reduce the rate of bone loss and fracture in adults [44]. The low dairy and calcium intake of Chinese subjects in this study might be related to the prevalent perception that calcium causes renal stones, the high prevalence of lactose intolerance among Malaysian Chinese [45], the absence of dairy products as ingredients in Chinese dishes, aversion of the taste [46], and concerns about weight gain and the fat/cholesterol content of some calcium-rich foods [47].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to understand the barriers for them to practice osteoprotective behaviors. Optimal physical activities, especially weight-bearing exercises, can increase bone mass and reduce osteoporosis risk [44]. However, most subjects in this study were minimally active.…”
Section: Discussionmentioning
confidence: 99%
“…Cross sectional studies have reported that the levels of osteoporosis knowledge in random, population-based samples are higher in younger ages and higher level of education also defines it [ 12 , 15 , 32 ]. This difference is visible in our study too.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that osteoporosis knowledge is one contributor to osteoporosis preventive behaviour [ 11 14 ]. The most important preventive strategies are increasing the level of physical activity at all ages, cessation of smoking, reduction of alcohol consumption, adequate dietary calcium and vitamin D intake [ 15 – 19 ]. Several studies have reported different levels of osteoporosis knowledge in random, population-based samples and these cross-sectional studies have found relation between levels of osteoporosis knowledge and osteoporosis preventive behaviours [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…That should be achieved through emphasizing on positive behaviors as appropriate intake of calcium and proteins, appropriate supplementation of vitamin C and D, increase of physical exercises, decrease consumption of caffeine, soda and smoking. [7,8] 1.1 Aim of the study The aim of this study was the assessment of university female workers' knowledge and health related behaviors regarding osteoporosis.…”
Section: Introductionmentioning
confidence: 99%